Biophysical aspects of mechanotransduction in cells and their physiological/biological implications in vocal fold vibration: a narrative review - Cha, Junseo; Thibeault, Susan L. (Frontiers in Cell and Developmental Biology, 2025)
Mechanotransduction is a crucial property in all organisms, modulating cellular behaviors in response to external mechanical stimuli. Given the high mobility of vocal folds, it is hypothesized that mechanotransduction significantly contributes to their tissue homeostasis. Recent studies have identified mechanosensitive proteins in vocal fold epithelia, supporting this hypothesis. Voice therapy, which, involves the mobilization of vocal folds, aims to rehabilitate vocal function and restore homeostasis. However, establishing a direct causal link between specific mechanical stimuli and therapeutic benefits is challenging due to the variability in voice therapy techniques. This challenge is further compounded when investigating biological benefits in humans. Vocal fold tissue cannot be biopsied without significant impairment of the vibratory characteristics of the vocal folds. Conversely, studies using vocal fold mimetic bioreactors have demonstrated that mechanical stimulation of vocal fold fibroblasts can lead to highly heterogeneous responses, depending on the nature and parameters of the induced vibration. These responses can either aid or impede vocal fold vibration at the physiological level. Future research is needed to determine the specific mechanical parameters that are biologically beneficial for vocal fold function.